The Post-Pandemic Plateau: A Provincial-Level Longitudinal Analysis of Tuberculosis Stagnation in Indonesia (2021–2023) - Adhika Rahman; Punik Mumpuni Wijayanti; Vita Widyasari (Community Medicine and Education Journal, 2025)
The COVID-19 pandemic caused profound disruptions to global tuberculosis (TB) control, particularly in high-burden nations. Indonesia, ranking second globally in TB burden, faces a critical recovery period. This study aims to characterize the epidemiological trajectory of TB in Indonesia during the post-pandemic phase (2021–2023), testing the hypothesis of stagnation versus recovery. We conducted a longitudinal ecological study utilizing Global Burden of Disease (GBD) estimates and national registry data. The dataset comprised 102 observations, representing a balanced panel of Indonesia’s 34 provinces across three years (2021, 2022, 2023). Variables included age-standardized prevalence per 100,000 population, mortality rates, and Human Development Index (HDI). Normality was assessed via the Shapiro-Wilk test. Correlations were analyzed using Spearman’s rank test for non-normal distributions. To account for unobserved spatial heterogeneity and provincial clustering, we employed a Fixed Effects Within-Group Panel Regression model to determine the independent effect of time on disease burden. The mean TB prevalence across the 34 provinces was 645.2 per 100,000 population (Standard Deviation 120.5), with a mean mortality rate of 38.4 per 100,000. Regional disparities were pronounced; Papua reported prevalence rates exceeding 1,000 per 100,000, while Bali remained below 350. The Fixed Effects regression model revealed that, after controlling for provincial heterogeneity, the passage of time from 2021 to 2023 was not significantly associated with a reduction in prevalence (beta = -1.24; p = 0.68) or mortality (beta = -0.05; p = 0.81). The model confirmed a Post-Pandemic Plateau, where metrics remained statistically unchanged despite the resumption of health services. In conclusion, TB control in Indonesia has entered a critical period of stagnation. The lack of a significant downward trend in the fixed-effects model suggests that post-pandemic recovery efforts have yet to neutralize the accumulated burden of missed diagnoses. Structural interventions targeting high-incidence provinces are urgently required to restart the decline.